Egg quality and productive performance of ISA Brown laying hens with grazing access - WingChing-Jones, Rodolfo (2023)
Introduction. Egg production systems are critical to food security. Concerns about animal welfare are increasing the interest in egg production systems with access to grazing. Objective. To describe the productive performances, morphological characteristics, and nutritional quality of the eggs from laying hens of the Isa Brown genetic line in a floor system with access to grazing. Materials and Methods. The research was carried out between July 2018 and January 2020 in the central canton of Turrialba, Cartago, Costa Rica, with hens of the Isa Brown genetic line with access to grazing. Productive performances were compared with the standard of the genetic line. External and internal morphological variables of the egg were evaluated and its nutritional content (dry matter, crude protein, ethereal extract, ash, calcium, phosphorus, saturated fatty acids (SFA), monounsaturated (MUFA), and polyunsaturated (PUFA) was characterized in hens of different ages. Results. The productive performances was not different from the genetic standard. The increase in bird age had a statistically significant influence on the increase in egg and shell weight, and the decrease in morphological index. Nutritional analysis indicated that increasing hen age decreased the dry matter content and the concentration of SFA and MUFA in the egg. The PUFA/SFA ratio of the eggs was higher than 0.45, regardless of the age of the laying hen. Conclusion. The productive indicators of the hens with access to grazing did not differ from ISA Brown genetic line standards for alternative systems. Egg weight, yolk index, Haugh units, and morphology index varied with the age of the hen.avicultura